Physical characteristics of splash and spray clouds produced by heavy vehicles (trucks and lorries) driven on wet asphalt. Issue 217 (October 2021) - Otxoterena Af Drake, Paul; Willstrand, Ola; Andersson, Anne; Biswanger, Henrik
Abstract: Heavy vehicles rolling on wet roads produce splash and spray clouds. These aerosols reduce the visibility of other drivers, contribute to a small, but quantifiable proportion of road traffic accidents and affect the operational capabilities of autonomous vehicles travelling near them. Even though knowing the physical properties of these aerosols is essential for testing and validating sensors for environment perception and recognition of autonomous vehicles, there is little information about them. In this work the physical characteristics of spray clouds produced by heavy vehicles rolling on wet asphalt were measured by optical methods. Time resolved droplet size, mass concentration, number density, light extinction and contrast attenuation parallel and perpendicular to the travelling direction of the vehicle were measured. Vehicle velocity, vehicle configuration and water depth were varied during the tests. Results show that the average droplet diameter ranges between 100 and 400 μ m with maximum diameters of almost 4 mm. Mass concentration gamuts between 0, 2 and 0, 7 kg/m 3 with peaks surpassing 1 kg/m 3 while number density spans between 20 and 40 cm − 3 and occasionally exceeds 100 cm − 3 . Light extinction can reach levels as high as 0, 2 m − 1 and contrast, evaluated from images, can reach values under 0, 1. Highlights: Water wheel splash from trucks and lorries were characterised by optical methods. Droplet size, number density and visibility parameters were studied. The dynamics of the aerosols show significant temporal variations during each test. Results can be used for modelling and testing sensors and autonomous vehicles.